The Level of Serum and Urinary Nephrin in Normal Pregnancy and Pregnancy with Subsequent Preeclampsia - Jung, Yun Ji (Yonsei Med J, 2017)
PURPOSE: The aim of this study was to evaluate serum and urinary nephrin levels of normal pregnancy to establish a standard reference value and to compare them with patients who subsequently developed preeclampsia (PE). MATERIALS AND METHODS: In this prospective study, 117 healthy singleton pregnancies were enrolled between 6 to 20 weeks of gestation at 2 participating medical centers during October 2010 to March 2012. Urine and serum samples were collected at the time of enrollment, each trimester, and at 4 to 6 weeks postpartum. Enzyme-linked immunosorbent assay for nephrin was performed and samples from patients who subsequently developed PE were compared to the normal patients. RESULTS: Of 117 patients initially enrolled, 99 patients delivered at the study centers and of those patients, 12 (12.1%) developed PE at a median gestational age of 34(+4) weeks (range 29(+5)–36(+6)). In the normal patients (n=68), serum nephrin level decreased and urinary nephrin level increased during the latter of pregnancy. In 12 patients who subsequently developed PE, a significant rise in the 3rd trimester serum and urinary nephrin levels, compared to the controls, was observed (p<0.001), and this increase occurred 9 days prior to the onset of clinical disease. CONCLUSION: As the onset of PE was preceded by the rise in the serum and urinary nephrin in comparison to normal pregnancy, serum and urinary nephrin may be a useful predictive marker of PE.